2,3-Dehydrokievitone combats methicillin-resistant Staphylococcus aureus infection by reducing alpha-hemolysin expression - Yu, Hangqian; Liu, Jingyu; Wang, Li; Guan, Shuhan; Jin, Yajing; Zheng, Jianze; Xiang, Hua; Wang, Dacheng; Liu, Dianfeng (Frontiers in Microbiology, 2022)
Due to powerful drug resistance and fatal toxicity of methicillin-resistant Staphylococcus aureus (MRSA), therapeutic strategies against virulence factors present obvious advantages since no evolutionary pressure will induce bacterial resistance. Alpha-hemolysin (Hla) is an extracellular toxin secreted by Staphylococcus aureus and contributes to bacterial pathogenicity. Herein, we screened a natural product 2,3-dehydrokievitone (2,3-DHKV) for inhibiting Hla activity of MRSA strain USA300 but not affecting bacteria growth. 2,3-DHKV significantly decreased hemolysin expression in a dose-dependent manner, but it did not potently neutralize hemolysin activity. Subsequently, cellular thermal shift and heptamer formation assays confirmed that 2,3-DHK affects hemolytic activity through indirect binding to Hla. RT-qPCR and western blot revealed that 2,3-DHKV suppressed Hla expression at the mRNA and protein levels, and further decreased agrA transcript levels. We also observed that 2,3-DHK significantly attenuated the damage of A549 cells by S. aureus and reduced the release of LDH. Moreover, in the MRSA-induced pneumonia mouse model, 2,3-DHK treatment prolonged the life span of mice and reduced the bacterial load in the lungs, which significantly alleviated the damage to the lungs. In summary, this study proved that 2,3-DHK as a Hla inhibitor is a potential antivirulence agent against MRSA infection.